Digital screening tool (Health Catch-UP!) to promote multi-disease screening in migrants. (20th October 2021) - Hargreaves, S; Carter, J; Knights, F; Deal, A; Goldsmith, L; Crawshaw, AF; Hayward, S; Zenner, D; Wurie, F; Hall, R
Abstract: Background: The ECDC has called for innovative strategies to deliver multi-disease screening (TB, LTBI, HIV, hepatitis B/C, Chagas, Strongyloidiasis and schistosomiasis) and catch-up vaccination (MMR, DTP) to adult migrants within the primary care context. We did a UK i qualitative study to explore current practice and seek views on a novel integrated digital tool to support delivery of screening recommendations for migrants https://emishealth.vids.io/videos/a49ad1bb1a18e4c72c/health-catch-up-with-requested-edits-mp4 ). Methods: Phase 1 was conducted via telephone with clinical primary care practitioners (PCPs) (phase 1) and informed data collection and analysis for phase 2 with administrative staff. Data were analysed iteratively, informed by thematic analysis (Ethics no.20/HRA/1674). Results: 64 participants were recruited in Phase 1 (25 general practitioners [GPs], 15 nurses, 7 healthcare assistants, 1 pharmacist); Phase 2 comprised administrative staff (11 Practice-Managers, 5 receptionists). There was lack of consistency in delivery of screening and vaccination. Most GP practices adopted a practice-specific approach, or had no system in place; screening only for HIV and hepatitis B/C. Barriers to screening were perceived lack of knowledge/training and limited financial resources. Facilitators included having an infectious disease/migrant-health champion, incentivisation, and clear protocols. Participants responded positively to the integrated Health Catch-UP! tool, confirming that it would increase screening and vaccination, reduce missed opportunities for preventative healthcare, and raise awareness of migrant health. Conclusions: Infectious disease screening and catch-up vaccination is not currently delivered well in primary care in high-migrant receiving European countries. Innovative digital tools like Health Catch-UP! could aid clinical decision-making and facilitating improved health outcomes for migrants. Further work is needed to evaluate this intervention. Key messages: Infectious disease screening and catch-up vaccination is not currently delivered well in primary care in high-migrant receiving European countries. Innovative digital tools could aid clinical decision-making and facilitating improved health outcomes for migrants.